Post flywheel squat potentiation of vertical and horizontal ground reaction force parameters during jumps and changes of direction - McErlain-Naylor, S. A.; Beato, M. (Sports, 2021)
(1) Background: The aim of the study was to determine the post-activation performance enhancement (PAPE) of vertical and horizontal ground reaction force parameters during jumps and change of direction following flywheel squat exercise using two different flywheel inertias. (2) Methods: Eleven male athletes performed a countermovement jump (CMJ), standing broad jump (SBJ), and "modified 505" change of direction (COD) in a control condition and 6 minutes following three sets of six repetitions of flywheel half squats at one of two inertias (0.029 kg·m2 and 0.061 kg·m2). Peak directional ground reaction force, power, and rate of force development were calculated for each test. (3) Results: Higher inertia flywheel squats were able to acutely enhance CMJ peak vertical force (Bayes Factor (BF10) = 33.5, very strong; d = 1.66; CI: 0.67, 2.70), whereas lower inertia flywheel squats were able to acutely enhance CMJ peak vertical power (BF10 = 3.65, moderate; d = 0.93; CI: 0.11, 1.88). The vertical squat exercise induced no PAPE effect on resultant SBJ or horizontal COD ground reaction force parameters, nor were any differences observed between the inertias. (4) Conclusions: Researchers and practitioners should consider the kinetic and kinematic correspondence of a pre-load stimulus to the subsequent sport-specific activity (i.e., flywheel squat to CMJ).